Hepatitis B vaccination in Burkina Faso: prevalence of HBsAg carriage and immune response in children in the western region - Armel Moumouni Sanou; Abdoul Kader Ilboudo; Clément Ziemlé Meda; Augustin Togozia; Abou Coulibaly; Assana Cisse; Tani Sagna; Dramane Kania; Zekiba Tarnagda (Journal of Infection in Developing Countries)
Introduction: Hepatitis B virus (HBV) infection remains a major health problem in Burkina Faso. To control and prevent HBV infection, Hepatitis B vaccine was introduced in the national expanded program in 2006. In this study, we evaluated the prevalence of HBsAg in children aged under 10 years after one decade of universal hepatitis B vaccination, and the immune response among these children.